Fear of Failure and Perfectionism in Sport - Correia, Marco Estêvão (Cuadernos de Psicología del Deporte, 2018)
Previous studies have reported consistent associations between fear of failure and perfectionism in sport. This study investigated how aspects of perfectionism in athletes (N = 350) were related to their fears of failure, and how perfectionism predicted different fears of failure. Structural equation modelling indicated strong correlations between perfectionism and fear of failure, especially on concern over mistakes dimension, reflecting the most negative aspect of the perfectionistic construct. Results concerning the structural model, where perfectionism was a predictor of fear of failure, also showed a positive and significant effect on fear of failure. Specifically, concern over mistakes influences significantly all fears of failure dimensions, followed by doubts about actions dimension. The findings demonstrate that concern over mistakes and doubts about actions are central in the relationship between perfectionism and fear of failure, being both recognized as the core aspects of perfectionism, predicting all fears of failure in athletes.